Characterization of histopathological lesions in a biological model for environmental studies: Eisenia andrei Bouché. Preliminar results - Vala, Helena (2016)
Introduction The strong expansion of the world production of plastics caused a severe accumulation of plastic debris in the environment, which makes them one of the most important contaminants, growing as a global environmental problem. Although the production in Europe has been relatively constant in the last 10 years, world plastic production continues to increase, affecting soil biota and their functions. Objectives Thus, in order to evaluate the effects of MP in soil-dwelling organisms, earthworms (Eisenia andrei Bouché), were exposed to standard artificial soil mixed with MPs and the authors documented, using microscopic figures, the pathological lesions found in this biological model. Material and Methods Eight adult earthworms extracted from soils contaminated with different concentrations of MP (mg/kgdw) with sizes ranging between 250-1000 m, were fixed in 10% neutral-buffered formalin and processed for routine histopathological diagnosis. Results and discussion Contrary to what would be expected, MP were not found throughout the GI tube of earthworms but several lesions were found in the individuals extracted from the soils with high MP concentrations, when compared with control group, namely epithelial intestinal atrophy and evidences of inflammatory responses to this stress agent. Conclusion Earthworms have probably avoided the consumption of the biggest MPs. However, evidences point for lesions that were likely caused by the smallest MPs that were likely egested during the depuration phase.